Making grandchildren : Is there an interest in becoming a grandparent? - Cutas, Daniela (Medicine, Health Care and Philosophy, 2025)
In recent decades, with the advancement of technologies facilitating reproduction, parents have been able to make decisions regarding their childrens’ reproductive potential: to preserve their fertility when threatened by genetic conditions or medical treatment; to use their gametes or embryos to make grandchildren; or even to collect their gametes posthumously and then use them to make grandchildren. While these interventions tend to be framed in terms of the interests of the children themselves, parents are not indifferent as to whether they become grandparents. At the same time, while the interest in becoming a parent and parents’ interests have been discussed extensively in reproductive and family ethics, grandparents and grandparenthood have been at best marginal in this growing literature. Against this background, I ask the question whether parents have an interest in becoming grandparents – and if so, which claims this interest generates against other parties (such as children themselves, healthcare professionals, or the state), if any. I explore possible paths towards conceptualising such an interest and the degree to which it could ground a claim to facilitate its fulfilment.
Keywords: grandparenthood; grandchildren; moral rights; interests; reproduction